2019
DOI: 10.1103/physrevb.100.104203
|View full text |Cite
|
Sign up to set email alerts
|

Many-body delocalization dynamics in long Aubry-André quasiperiodic chains

Abstract: We study quench dynamics in an interacting spin chain with a quasi-periodic on-site field, known as the interacting Aubry-André model of many-body localization. Using the time-dependent variational principle, we assess the late-time behavior for chains up to L = 50. We find that the choice of periodicity Φ of the quasi-periodic field influences the dynamics. For Φ = ( √ 5 − 1)/2 (the inverse golden ratio) and interaction ∆ = 1, the model most frequently considered in the literature, we obtain the critical diso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 63 publications
(119 reference statements)
9
80
0
Order By: Relevance
“…This is also motivated by similar studies on quenched disordered systems that found a linear drift in critical disorder strength with increasing length [20,37,60]. While few previous studies have commented on this behavior being relatively weak for QP systems (thus emphasizing that QP systems are relatively stable) [69,77,81], to the best of our knowledge these have not been based on substantial quantitative arguments.…”
Section: Finite-size Scaling Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…This is also motivated by similar studies on quenched disordered systems that found a linear drift in critical disorder strength with increasing length [20,37,60]. While few previous studies have commented on this behavior being relatively weak for QP systems (thus emphasizing that QP systems are relatively stable) [69,77,81], to the best of our knowledge these have not been based on substantial quantitative arguments.…”
Section: Finite-size Scaling Analysismentioning
confidence: 92%
“…The distribution P (ε) has characteristic peaks at = ±2π sin(πk). The value of ε determines how resonant the local tunneling is, strongly affecting system properties both for non-interacting models [94] as well as for the MBL transition [69]. It seems reasonable to us that the characteristic shape of P (ε) for the QP potential determines the double peak structure of P(s z ).…”
Section: Model and Observablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments of quantum simulation based on ultracold atoms [5][6][7][8][9], trapped ions [10], and superconduction circuits [11][12][13][14] with small coupling to thermal environment pave the way for studying MBL in large-scale systems beyond classical exact diagonalization calculations. Several characteristic dynamical properties of MBL, such as the logarithmic spreading of entanglement entropy (EE) [11,[15][16][17][18][19][20] and quantum Fisher information [10,21,22], and the power-law decay of imbalance [5][6][7][8][23][24][25][26], are observed.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of rare regions (like in quasiperiodic systems), however, one therefore expects only diffusive transport all the way to the MBL transition. Indeed for the interacting AAH model [40][41][42][43][44][45][46][47][48][49][50][51][52][53] , this was to a certain extend observed 48,50 , see however e.g. Refs.…”
Section: Introductionmentioning
confidence: 99%